تأثير تمرينات خاصة في تنمية بعض القدرات المركبة والمهارات الهجومية بكرة القدم للصالات - محمود وادي حسین (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص یھدف البحث الى اعداد تمرینات خاصة ومدى فاعلیة ھذه التمرینات في تنمیة بعض القدرات الحركیة والمھارات الھجومیة بكرة القدم للصالات ، واستخدم الباحث المنھج التجریبي ، اما عینة البحث فقد تضمنت منتخب تربیة دیالى للمراحل الابتدائیة للبنین والبالغ عددھم ( ١٢ ( لاعب وبالطریقة العمدیة نظرا ً لتعاون المدرب واللاعبین مع الباحث وتم استخدام الاختبارات المرشحة من قبل الخبراء المختصین وبعد استخدام الوسائل الاحصائیة المناسبة توصل الباحث الى استنتاجات أھمھا ان طبیعة التمرینات المختارة تتناسب مع امكانیة العینة مما ادى الى زیادة الدافعیة بالعمل ، وان استخدام التمرینات المتنوعة في مرحلة الاعداد الخاص لھُ الاثر الایجابي والفعال في تطویر بعض مكونات القدرات الحركیة والمھارات الھجومیة بكرة القدم للصالات . وان تكرار التمرینات والتدرج بھا من السھل الى الصعب ومن البسیط الى المركب وفق اسس علمیة لھا تأثیر ایجابي في تطویر بعض القدرات الحركیة والمھارات الھجومیة بكرة القدم للصالات . ومن اھم التوصیات التي توصل الیھا الباحث ھي اتباع الاسلوب العلمي عند اختیار التمرینات للوحدة التدریبیة مع مراعاتھا لطبیعة وخصائص اللاعب ومراعاة مبدأ الفردیة بالتدریب . واختیار التمرینات الملائمة للمرحلة العمریة لامكانیة الاداء بالشكل الصحیح والذي یساعد في تنمیة القدرات الحركیة والمھارات الھجومیة بكرة القدم للصالات . Impact exercises, especially in the development of some motor skills and offensive skills football to Eat By Mahmoud Wady Master's student/ Sport Education College /University Of Diyala Abstract The research aims to prepare exercises especially the effectiveness of their exercise in the development of some motor skills and skills offensive football to Eat, the researcher used the experimental method, either the research sample included the team breeding Diyala stages Primary School for Boys and numbered (12) for the player and the way intentional due to the cooperation of the coach and players with researcher was used tests candidate by experts and after using the means appropriate statistical researcher reached conclusions notably the nature of the exercises selected commensurate with the possibility of the sample, which led to increased motivation to work, and that the use of exercise varied in the preparation stage for a positive impact and effective role in the development of some components capacity and motor skills offensive football Eat. And repeat the exercise and the gradient is easy to difficult, from simple to complex according to scientific foundations have a positive influence in the development of some motor skills and offensive skills football Eat. One of the most important recommendations reached by the researcher is to follow the scientific method when choosing a training exercise of the unit with the observance of the nature and characteristics of the player and the observance of the principle of individual training.